Building Life Around the Foster Home vs. Moving On: The Competing Needs of People Living in Foster Homes - Piat, Myra (Psychiatr Rehabil J, 2008)
Amid the current shift toward more autonomous housing for mental health consumers, people living in psychiatric foster homes in Montreal, Canada articulated complex concerns over what type of housing would best meet their present and future needs. Semi structured interviews were conducted with 33 residents. Consumers describe the tensions associated with foster home life. Two overall competing needs emerged: the need to build their lives around the foster home and the need to build life beyond the foster home. Residents describe their need for security and support versus their need for greater personal autonomy, the dilemmas associated with communal living, and their struggle to envisage a positive future. Housing arrangements, as well as the relationships and patterns of support that develop there, are critically important for residents. Mental health professionals mandated to dismantle foster homes for more autonomous housing need to take this reality into account.